2013
DOI: 10.4304/jmm.8.3.299-305
|View full text |Cite
|
Sign up to set email alerts
|

A Combined DWT and DCT Watermarking Scheme Optimized Using Genetic Algorithm

Abstract: To protect the copyright of digital image, this paper proposed a combined Discrete Wavelet Transform (DWT) and Discrete Cosine Transform (DCT) based watermarking scheme. To embed the watermark, the cover image was decomposed by a 2-level DWT, and the HL2 sub-band coefficient was divided into 4x4 blocks, then the DCT was performed on each of these blocks. The watermark bit was embedded by predefined pattern_0 or pattern_1 on the middle band coefficients of DCT. After watermark insertion, inverse DCT was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In order to evaluate the robustness against JPEG compression, we compressed the watermarked images "Mandrill", "Peppers", "cameraman", "Lena" and "Goldhill" by different quality factors and we summarize the average NC values for the five test images. Afterwards, we compare our scheme to [11] and [12]. Table IV shows the NC values, which are almost close to 1, obtained after JPEG attack with their corresponding PSNR values in the case of "Mandrill".…”
Section: B Robustness Against Attacksmentioning
confidence: 66%
See 2 more Smart Citations
“…In order to evaluate the robustness against JPEG compression, we compressed the watermarked images "Mandrill", "Peppers", "cameraman", "Lena" and "Goldhill" by different quality factors and we summarize the average NC values for the five test images. Afterwards, we compare our scheme to [11] and [12]. Table IV shows the NC values, which are almost close to 1, obtained after JPEG attack with their corresponding PSNR values in the case of "Mandrill".…”
Section: B Robustness Against Attacksmentioning
confidence: 66%
“…Table IV shows the NC values, which are almost close to 1, obtained after JPEG attack with their corresponding PSNR values in the case of "Mandrill". It can be seen from Table VII and Table VIII that our method gives better results than approaches in [11] and [12]. According to Table III, it can be observed that our method is robust against noising attack and gives better results.…”
Section: B Robustness Against Attacksmentioning
confidence: 71%
See 1 more Smart Citation
“…The objective function is the linear sum of three objectives: visual quality, robustness, and amount of embedded information. Mingzhi and Yan (Mingzhi et al, 2013) proposed a combined DWT and Discrete Cosine Transform (DCT) scheme (Rao and Yip, 1990), based on a watermarking scheme optimized by genetic algorithm (GA) (Goldberg, 1989). In this method, fitness calculations are performed on images corrupted by attacks, such as JPEG compression, Gaussian filtering, image sharpening, and cropping.…”
Section: Related Workmentioning
confidence: 99%
“…These algorithms are fragile to manipulations, but they have little computation work and can be easily implemented. The transform domain watermarking schemes are mainly concentrated on some signal transforms such as DCT(Discrete Cosine Transform) [5,6], DFT(Discrete Fourier Transform) [7] and DWT(Discrete Wavelet Transform) [8][9][10], etc. The watermark is embedded into the host by modifying some or all frequency domain coefficients, especially middle frequency coefficients.…”
Section: Introductionsmentioning
confidence: 99%